Identifying novel mechanisms of abdominal aortic aneurysm via unbiased proteomics and systems biology - Morgan, Stephanie; Lee, Lang Ho; Halu, Arda; Nicolau, Jessica S.; Higashi, Hideyuki; Ha, Anna H.; Wen, Jennifer R.; Daugherty, Alan; Libby, Peter; Cameron, Scott J.; Mix, Doran; Aikawa, Elena; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background Abdominal aortic aneurysm (AAA), characterized by a continued expansion of the aorta, leads to rupture if not surgically repaired. Mice aid the study of disease progression and its underlying mechanisms since sequential studies of aneurysm development are not feasible in humans. The present study used unbiased proteomics and systems biology to understand the molecular relationship between the mouse models of AAA and the human disease. Methods and results Aortic tissues of developing and established aneurysms produced by either angiotensin II (AngII) infusion in Apoe−/− and Ldlr−/− mice or intraluminal elastase incubation in wildtype C57BL/6J mice were examined. Aortas were dissected free and separated into eight anatomical segments for proteomics in comparison to their appropriate controls. High-dimensional proteome cluster analyses identified site-specific protein signatures in the suprarenal segment for AngII-infused mice (159 for Apoe−/− and 158 for Ldlr−/−) and the infrarenal segment for elastase-incubated mice (173). Network analysis revealed a predominance of inflammatory and coagulation factors in developing aneurysms, and a predominance of fibrosis-related pathways in established aneurysms for both models. To further substantiate our discovery platform, proteomics was performed on human infrarenal aortic aneurysm tissues as well as aortic tissue collected from age-matched controls. Protein processing and inflammatory pathways, particularly neutrophil-associated inflammation, dominated the proteome of the human aneurysm abdominal tissue. Aneurysmal tissue from both mouse and human had inflammation, coagulation, and protein processing signatures, but differed in the prevalence of neutrophil-associated pathways, and erythrocyte and oxidative stress-dominated networks in the human aneurysms. Conclusions Identifying changes unique to each mouse model will help to contextualize model-specific findings. Focusing on shared proteins between mouse experimental models or between mouse and human tissues may help to better understand the mechanisms for AAA and establish molecular bases for novel therapies.